Co-creating a gamified app for enhancing students' emotional resilience in times of crisis (COVID-19) - Nicolaidou, Iolie; Aristeidis, L.; Christodoulou, C.; Lambrinos, Lambros (My University, 2021)
COVID-19 resulted in the implementation of severe restrictions in movement and enforcement of social distancing measures globally. Students are considered as a population with heightened pre-existing stress levels; being a vulnerable group, the COVID-19 pandemic, has placed an unprecedented mental health burden on them. Studies conducted since the outbreak of the pandemic uncovered a significant elevation of COVID-19 related anxiety among students in European countries. This urgently requires further examination and immediate interventions to strengthen students’ resilience and help them cope during future lockdown measures applied due to the pandemic. There is a need for a mobile learning application, which does not require F2F instruction. Students have continuous access to their mobile phones and typically enjoy playing mobile games. The present study, therefore, suggests the design and development of a gamified mobile application, based on self-determination theory, to encourage students to follow experts’ guidelines for coping with a crisis. This pilot study attempted to document the extent to which undergraduate students experience anxiety during moderate precautionary measures due to the COVID19 pandemic and to evaluate the described intervention’s feasibility. The research questions were: a) To what extent did students experience anxiety during moderate precautionary measures due to the COVID19 pandemic? and b) How do students evaluate the feasibility of the design for a gamified app about resilience? An anxiety measurement was completed by 71 students in a European public university. A subset of them (n=18) participated in a 2-hour online, participatory design session and evaluated the feasibility of the idea for a gamified app regarding resilience. Students evaluated specific gamification elements, such as system recommendations, the use of sensors, the allocation of points, competition, and collaboration among users, reflection, and goal setting. Their ideas about the strengths and weaknesses of the app were also discussed. There were three data sources: a) the General Anxiety Disorder-7 (GAD-7) scale, a self-reporting instrument for anxiety, b) a questionnaire consisting of 12 statements on a 5-point Likert scale and two open-ended questions, and c) the recorded participatory design session. With respect to the first research question, findings revealed that 33.9% of students reported moderate to severe anxiety symptoms experienced under non-extreme lockdown measures. This percentage is higher than the respective percentage measured with the same instrument during extreme lockdown measures (23.1%) in the same country, and as such, it is a finding that intensifies concerns expressed about students’ anxiety levels in the literature. Concerning the second research question, students evaluated suggested gamification elements positively (with means exceeding 3.6 out of 5 for recommendations, points, collaboration, reflection, and goals). Goal setting and collaboration elements among users received the highest scores (M=4.06 and M=3.94, respectively). The use of sensors (M=3.06) as well as the use of competitive elements among users (M=3.11) received the lowest scores. This pilot study verified that students’ anxiety levels remain high, even during non-extreme lockdown measures. It also showed that a gamified application aiming to support resilience is perceived rather positively by the students it targets.
Keywords: Gamified app; Resilience; Mental health; Participatory design; Higher education